Analysis of the Social Environment of Out-of-School Children in Lambara Hamlet, Kasano Village, Baras Subdistrict, Pasangkayu Regency - Liramadani; Ardillah Abu; Rahmadiani Rahmadiani (JURNAL PENDIDIKAN IPS, 2025)
This study aims to analyze the social environment conditions of junior high school-aged children who dropped out in Dusun Lambara and to identify the social environmental factors influencing their decision to leave school. This research is a field study employing a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation. Data analysis is conducted through data reduction, data presentation, and verification. The results indicate that the social environment of junior high school-aged children who dropped out tends to be negative, with minimal parental support, weak school supervision, and peer influence—particularly from friends who have also dropped out—being the main triggers. The children feel freer outside of school and engage in activities such as hanging out, playing games, or doing odd jobs. Other contributing social factors include family economic pressure, low parental education levels, lack of emotional support, as well as limited access to education due to the distant school location, poor road infrastructure, and lack of public transportation. A permissive social environment toward dropping out further strengthens these decisions. The key finding of this study is that children’s decisions to drop out are heavily influenced by the complex interactions among family factors, school conditions, peer groups, and the surrounding socioeconomic context. The implications of this research emphasize the need for active involvement from families, schools, village governments, and community leaders in creating a social environment that supports the continuity of education for junior high school children in Dusun Lambara.